THE IMPLEMENTATION OF JAPAN-PHILIPPINES MARITIME DIPLOMACY AS PROACTIVE APPROACH TO RESPOND TO THE ASSERTIVE CHINA IN SOUTH CHINA SEA (2012-2017) - Ivena Erwandi, Anak Agung Banyu Perwita, (Jurnal Mandala, 2018)
Nowadays, the South China Sea has been identified with increasing defense spending and military modernization of the neighboring countries which are driven by China’s assertiveness in the region. China’s assertive behavior in the South China Sea is an expression of its growing ambition over the region which is part of its core interests. China’s assertiveness is buoyed by its significant military presence and power projection in the region. Japan and the Philippines are having converging threat perceptions towards China’s assertiveness in the South China Sea as well as sharing common interests to balance the assertive China. Contested with China’s assertive behavior, since 2012, Japan and the Philippines have been conducting dynamic maritime diplomacy in order to safeguard the status quo of the sea from the assertive China. The implementation of Japan-Philippines maritime diplomacy in responding to China’s assertiveness in South China Sea is a form of “proactive approach” by Japan, following the “Proactive Contribution to Peace” banner resounded under Prime Minister Shinzo Abe administration. The proactive approach in this research features the concept of “balance of power” and “cooperative maritime diplomacy”.